Characterization and effect of optimized spray-drying conditions on spray-dried coriander essential oil - Rahim, Muhammad Abdul (2024)
Coriander (Coriandrum sativum L.) essential oil (CEO) has many beneficial features, including antimicrobial and antifungal properties along with good aroma. It also has an important role in food processing and preservation. However, CEO is highly volatile and sensitive to external factors (heat, light and oxygen), as well as susceptible to lipid oxidation due to environmental and general processing conditions. This limits water solubility, making it difficult to incorporate CEO into aqueous food matrices, which further limits their industrial application. Spray-drying encapsulation may prevent CEO oxidation, increase CEO oxidative stability and improve their physicochemical properties. In this study, spray-dried CEO (SDCEO) was prepared using a mini laboratory-scale spray-dryer and the processing conditions were optimized. The SDCEO were characterized in respect to free fatty acids (FFA), peroxide values (PV), fatty acid (FA) profiles, Fourier-transform infrared spectroscopy (FTIR) and physical morphology by scanning electron microscopy (SEM). Results indicated that the maximum value of FFA, PV, fatty acid composition (including petroselinic, linoleic and oleic acids) in SDCEO were observed at the following spray-drying conditions: an inlet-air temperature (IAT) of 140 °C, needle speed (NS) of 2 s and the wall-material (WM) at 25%. The minimum values were observed at an IAT of 180 °C, NS of 4 s and WM of 30%. Analysis of variance and the interaction effects of independent factors showed that IAT and WM significantly positively influenced the response for good oxidative stability. Thus, SDCEO is likely to be used as a natural active ingredient in the food processing, cosmetic, nutraceutical and pharmaceutical industries with high stability, and may be stored for a long time without evaporation or oxidation.